A New Diphenylethylene from Arundina graminifolia and Its Cytotoxicity - Gao, Yan; Jin, Yongcan; Yang, Shuai; Wu, Jiao; Gao, Xuemei; Hu, Qiufen; Ma, Yinhai (Asian Journal of Chemistry, 2014)
A new diphenylethylenes, gramniphenol J (1), was isolated from Arundina graminifolia. Its structure was elucidated by spectroscopic methods including extensive 1D- and 2D-NMR techniques. Compound 1 was evaluated for its cytotoxicity against five human tumor cell lines and showed cytotoxicity against PC3 and SHSY5Y cells with IC50 values of 8.2 and 7.6 μM.